Gender typifications and the experiences of survivors of child sexual abuse by female perpetrators: A qualitative analysis. - Denov, Myriam. (University of Ottawa (Canada), 1996)
As a result of contemporary North American culture's reliance on the gender typifications that females are nurturing, sexually passive, and frequent victims of abuse, and that males are assertive, sexually aggressive, and frequent perpetraturs of abuse, people are more likely to perceive of females in the role of sexual abuse victims and males in the role of sexual abuse perpetrators. Furthermore, males are assumed to enjoy or profit from any form of sexual contact with females, and females are assumed to be incapable of causing harm through coercive sexual contact. This study demonstrates that such gender typifications overlook other "atypical" or "deviant" realities, namely the reality where females are perpetrators of sexual abuse and males or females are their victims. Moreover, the experiences of victims of sexual abuse by females clearly defy conventional gender typifications. Their reported experiences reveal that females can he perpetrators of sexual abuse, males can be sexually victimized by females, males do not enjoy or profit from coerced sexual contact with females, and that there can be varying degrees of psychological harm following coerced sexual contact with a female. Finally, this study reveals that there are consequences to opposing gender typifications. The survivors of sexual abuse in this study faced negative consequences as a result of reporting a reality that defied the "typical". Participants maintained that professionals, be they, police officers, child protection agents and mental health professionals, responded to their claims of sexual abuse with shock, disbelief, and denied their victimization and injury as a result of the gender of their sexual abuse perpetrator. Professionals often renegotiated the behaviours of alleged female perpetrators so that they were more consistent with conventional gender roles. According to respondents, the responses of professionals' heightened their feelings of self-blame, denial, resignation, anger and helplessness. (Abstract shortened by UMI.)
Keywords: Women's Studies.